Extra-adrenal composite phaeochromocytoma/neuroblastoma in a 15-month-old child - Tom Monclair; Ellen Ruud; Henrik Holmstrøm; Ingegerd Aagenæs; Marius Asplin; Klaus Beiske (Elsevier, 2015)
A 15-month-old boy was diagnosed with malignant hypertension caused by a catecholamine excreting retroperitoneal paraganglioma consisting of a composite phaeochromocytoma/differentiating neuroblastoma. After alpha-blockade the tumor was excised. No adjuvant treatment was given, and he is doing well eight years after the diagnosis. The patient is the first child known to have an extra-adrenal retroperitoneal composite tumor, and also the youngest child with a composite phaeochromocytoma/neuroblastoma reported in the English literature.